Determinants of Sustainability Assurance Level: Evidence from Energy Companies in Asia - Saprida Khoirotunnisa; Maylia Pramono Sari (Journal of Applied Accounting and Taxation, 2026)
This research highlights the elements that impact corporate decision-making pertaining to the degree of sustainability assurance among enterprises operating within the Asian energy sector. In light of the escalating demands for the enhancement of transparency and accountability within sustainability disclosures has led to the identification of the assurance level as a crucial instrument for enhancing the veracity of environmental, social, and governance (ESG) disclosures. Utilizing panel data derived from energy firms monitored throughout the duration of the study, this investigation employs panel data regression analysis, specifically estimated via Panel Least Squares methodology. The extent of sustainability assurance—delineated into no assurance, limited assurance, and reasonable assurance—operates as the dependent variable within the analytical framework, the independent variables are constituted by the attributes of the assurance provider, the extent of media pressure, various dimensions of board size, and the independence of the audit committee, with profitability, operationalized through return on assets (ROA), the inclusion of a control variable is warranted. The empirical results suggest that the characteristics of assurance providers, the degree of media pressure, and profitability have a positive and statistically significant effect on the assessment of the level of sustainability assurance. Corporations that engage the services of Big Four assurance firms, experience intensified media scrutiny, and demonstrate superior financial performance are more predisposed to opt for a reasonable assurance level. In contrast, the dimensions of the board and the autonomy of the audit committee do not demonstrate a statistically significant association with the selection of assurance level. These findings indicate that external pressures and financial capacity are more influential drivers of higher sustainability assurance levels than internal governance attributes. Overall, this study offers relevant insights for firms, regulators, and stakeholders seeking to strengthen sustainability assurance practices and enhance the legitimacy and credibility of ESG reporting.